FAKTOR YANG PALING BERHUBUNGAN DALAM PEMBERIAN SUSU FORMULA ADALAH STATUS PEKERJAAN IBU BAYI - Wijayanti, Reny; Mawarti, Retno; Susanti, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background:The coverage of exclusive breast-feeding in Yogyakarta is only 40,57%, which is not in accordance with the target of 80% from the Ministry of Health. This is related to factors associated with formula feeding in infants aged 6-12 month, namely mothers’ education, knowledge, occupation, and income. Objective: This study aimed to determine the most dominant factor in the formula feeding in infants aged 6-12 months in Selo Posyandu. Methods:This study was a quantitative research, with cross-sectional design. The number of samples was 36 respondents from Selo posyandu. Instrument in this study was a questionnaire. Data were analysed using chi-square test and Kendall’s tau test with a significance level of p<0.05. Results: Factors associated with formula feeding was education (p=0.004), knowledge (p=0.001), income (p=0.029), employment status (p=0.003) and the multivariate test showed that the most dominant factor was mothers’ employment status. Conclusion: The most pertinent factor in the formula feeding in infants was mother's employment status. Keywords: baby 6-12 months, factors, formula feeding